Advanced nutrient monitoring: Cost-effective cerium ion detection with smart device integration - Revathy Raghunathan Lekshmy (22046402) (2024)
This research is critically important for large-scale poultry farming, where vigilant monitoring is necessary to assess nutrient levels in poultry feed. Detecting cerium in poultry feed through colorimetric techniques is crucial for evaluating nutrient intake, feed quality, animal health, and broader environmental impacts. This study significantly contributes to ongoing research and monitoring efforts, aiding in maintaining an optimal mineral balance and enhancing chicken quality and overall poultry performance. The study utilized Alizarin Red dye (AR), both individually and in combination with Eriochrome Black T (EBT), to identify the presence of cerium ions. Various experimental conditions such as pH, concentration, temperature, and specificity were thoroughly examined. The UV-Vis absorption spectra indicated that the average minimum detectable limit for cerium ions is approximately 5 ppm, with a detection range of 0.2–3 mM. Additionally, a cost-effective paper-based sensor and a portable colorimetric method for detecting cerium ions were innovatively designed. This paper-based sensor ensures precise detection at room temperature, demonstrating high sensitivity and selectivity. The detection system was integrated with smart devices, enabling the swift capture of Red, Green, and Blue (RGB) values for practical real-time applications. This integration allows for rapid on-site identification of cerium ions. The introduction of this affordable, accurate, and portable colorimetric method for monitoring cerium ions represents a promising advancement in developing accessible tools within this field. Other Information Published in: Biochemical Engineering Journal License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.bej.2024.109409